Upaya PT. Serba Digital Dalam Membangun Brand Awareness Produk Costa - Jasmine Ramadhany Karim; Pramesti, Ajeng Arieska; Awwalin, Cahya Aulia; Tamunu, Fernando Sadrakh; Kurniasari, Ni Gusti Ayu Ketut (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2024)
This research aims to analyze PT Serba Digital's strategies and efforts in increasing brand awareness of Costa products, which include camera accessories such as lighting, tripods, and microphones. PT Serba Digital uses various marketing tactics, both digital and conventional, to expand brand awareness among consumers. These strategies include the use of social media, collaboration with influencers, creative content creation, and integrated promotional campaigns. Social media, especially platforms such as Instagram and TikTok, were used as key tools to reach a wider and more diverse audience. Collaborations with well-known influencers and content creators also have a significant impact in expanding the reach of Costa's products. In addition, PT Serba Digital utilizes data analytics to measure the effectiveness of the campaign and adjust strategies based on market response. This study uses qualitative research methods using Kotler and Keller's theory of Brand Awareness. The results showed that these efforts were successful in increasing brand awareness of Costa's products, which was characterized by increased interactions on social media, growth in the number of followers, as well as increased product sales. This study provides important insights for other companies in the camera accessories industry looking to increase brand awareness through innovative and effective marketing strategies.